Analyzing the barriers beyond halal certifications using Z-score functions of hesitant fuzzy DEMATEL / Muhammad Syakir Abdul Razak, Nurul Hidayah Bahrin and Puteri Nur Sabrenna Asmawi - Abdul Razak, Muhammad Syakir; Bahrin, Nurul Hidayah; Asmawi, Puteri Nur Sabrenna (2023)
A halal certificate is an acknowledgment granted to commercial companies that have complied with the halal standards outlined in the Malaysian Halal Management System (MHMS) 2020 and Manual Prosedur Pensijilan Halal Malaysia, MPPHM (Domestic) 2020. The use of a halal emblem by a company to identify between halal-guaranteed and non-guaranteed halal products is permitted by a halal certificate. The most likely reason for this trend is increased the Halal Executives’ dissatisfaction during halal certification process. Everyone has a different viewpoint, so it is challenging to come up with a concrete solution to the problem. Besides, there is no previous studies that use hesitant fuzzy DEMATEL to analyze halal certification in Malaysia. Also, every method that used in some application need to validate first with determine an applicability of the test result. In that case, this study aims to propose the Z-score function of hesitant fuzzy DEMATEL on analyzing the barriers beyond halal certifications, to determine the causes and effects of barriers to halal certification adoption through the proposed method, and to validate the robustness of our proposed method. Steps of methodology in this study have two parts which contain google form to collect data from respondents, and other part is using hesitant fuzzy DEMATEL based on the experts in halal certification. The result of this study shows that the using fake Halal logo is the most common in Halal certification criteria based on ranking by hesitant fuzzy DEMATEL method.